HIGH PLASMA TNF-? LEVELS AND MONONUCLEAR CELLS iNOS AND TNF-? EXPRESSION AS RISK FACTORS FOR PAINFUL DIABETIC NEUROPATHY - Eko Purwata, Thomas; Suastika, Ketut; Raka Sudewi, A. A.; Widjaja, Djoenaidi (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 4, No. 2 Juli 2010)
Painful Diabetic Neuropathy (PDN) is one of the most common and annoyingcomplications of diabetes mellitus. The pathogenesis of PDN is complex and still unclear.Recently it has become clear that nitric oxide (NO) and proinflammatory cytokines playan important role in the pathogenesis and maintenance of pain in PDN. Based on thisphenomenon, this study was conducted to investigate whether the cytokine tumornecrosis factor-alpha (TNF-?) and NO, in this case inducible Nitric Oxide Synthase(iNOS), play a role in PDN pathogenesis.The study was carried in two steps. The first step was a cross sectional and thesecond step was a case-control study. The study was performed in 110 type-2 diabeticpatients. The plasma TNF-? levels were determined by ELISA while the expression ofTNF-? and iNOS in mononuclear cells were analyzed immunohistochemically.Of 110 subjects, 59 patients suffered from Painful DN (case) and the remaining51 patients were Painless DN (control). Cross sectionally, plasma TNF-? levels andimmunoreactivity for iNOS and TNF-? were higher in patients with more severe pain inthe Visual Analog Scale (VAS). There were statistically significant differences (p <0.05) between mild and severe pain in regard to TNF-? level (15.24 pg/ml ± 5.42 vs.20.44 pg/ml ± 10.34 ); to iNOS immunoreactivity (9.72 % ± 8.61 vs. 15.6% ± 11.84); andto TNF-? immunoreactivity (13.0 % ± 9. 48 vs. 20.44% ± 11.75).The case control study showed that TNF-? had an odd ratio of 5.053 [CI 95%(2.241-11.392); p < 0.001]. TNF-? immunoreactivity of 4.125 [CI 95% (1.805-9.425); p< 0.001]; and iNOS immunoreactivity of 3.546 [CI 95% (1.613-7.795); p = 0.002]. There were correlations between TNF-? level, TNF-? and iNOS immunoreactivity andVAS with coefficient correlation: 0.330; 0.285 and 0.275 (p < 0.05) respectively.It is concluded that Diabetic Neuropathy patients with high TNF-? levels, iNOSand TNF-? immunoreactivity of mononuclear cells have higher risk for painful DN thanpainless DN. The higher TNF-? level, iNOS and TNF-? immunoreactivity the moresevere was the pain. This supports the hypothesis that TNF-? and iNOS have role inPDN pathogenesis. The results of this research could be applied as a basic for furtherresearch in pursuit of better management of PDN.
Keywords: Painful Diabetic Neuropathy, TNF-?, iNOS, Visual Analog Scale